From Zuzanna Bier-Korngold to Suzanne Pacaud, that is about intellectual fortunes of Polish Jewess - Smywińska-Pohl, Anna (Biografie nieoczywiste: Przełom, kryzys, transgresja w perspektywie interdyscyplinarnej, 2018)
This article presents Zuzanna Bier-Korngold’s biography and thought. She was a philosopher and psychologist who emigrated to France in the1920s and then became Suzanne Pacaud. In the field of philosophy she was dealing with the theory of art and in the field of psychology she conducted research in psychotechnic, ergonomy and ageing. Her biography and scientific life is interesting because of several reasons. First of all, she could not develop her career because of discrimination based on sex and race (she was a Jewess). Fortunately, she decided to move to France, where she achieved a significant success. Her life and works are unknown in Poland and her texts have not been translated into Polish.